Approval of Coercion in Psychiatry in Public Perception and the Role of Stigmatization - Steiger, Sahar; Moeller, Julian; Sowislo, Julia F.; Lieb, Roselind; Lang, Undine E.; Huber, Christian G. (Frontiers in Psychiatry, 2022)
Background: Coercion is routinely used in psychiatry. Its benefits and drawbacks are controver-sially debated. In addition, the majority of persons with mental health problems are exposed to stigmatization and are assumed to be dangerous. Stigmatization is associated with negative con-sequences for individuals with mental illness such as disapproval, social rejection, exclusion, and discrimination. Being subjected to coercive measures can increase the stigmatization of the af-fected persons, and stigmatization might lead to higher approval for coercion. Aims of the study: This study aims to examine the approval for coercive measures in psychiatry by the general public, and to explore its relation with person- and situation-specific factors as well as with stigmatization. Method: We conducted a representative survey of the general population (N =2207) in the can-ton of Basel-Stadt, Switzerland. Participants were asked to read a vignette depicting psychopatho-logical symptoms of a fictitious character and indicate whether they would accept coercive measures for the person in the vignette. Desire for social distance and perceived dangerousness were assessed as measures of stigmatization. Findings: The person in the case vignette exhibiting dangerous behavior, showing symptoms of a psychotic disorder, being perceived as dangerous, and treatment being understood as helpful increased approval of coercion in general, while familiarity of the respondents with mental illness decreased approval. Conclusions: The public attitude regarding the approval of coercion in psychiatry is highly differ-entiated and largely follows the current legal framework and medical treatment guidelines. High-er approval occurred in situations of self-harm or harm to others and when coercive measures were thought to have a beneficial effect for the affected persons. A considerable part of the ap-proval for coercion is predicted by stigmatization. With the increasing severity of coercive measures, the influence of person- and situation-specific factors and of familiarity with mental illness decreased and generalizing and stigmatizing attitudes became stronger predictors for the approval of more severe measures.